2017
DOI: 10.1039/c7cy00291b
|View full text |Cite
|
Sign up to set email alerts
|

Addressing stability challenges of using bimetallic electrocatalysts: the case of gold–palladium nanoalloys

Abstract: Studying changes in surface composition of bimetallic (AuPd) catalysts under dealloying is of key importance for predicting their stability during application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 83 publications
0
46
0
Order By: Relevance
“…GC/Zn‐MOF electrode does not show any peak in the selected potential window (0.2 to 1.1 V). However, the GC/Au@Zn‐MOF shows a pair of peaks which represent the formation of surface gold oxide and its reduction . This clearly shows the successful incorporation of Au NPs into Zn‐MOF and its viability for the electrocatalytic reactions.…”
Section: Resultsmentioning
confidence: 99%
“…GC/Zn‐MOF electrode does not show any peak in the selected potential window (0.2 to 1.1 V). However, the GC/Au@Zn‐MOF shows a pair of peaks which represent the formation of surface gold oxide and its reduction . This clearly shows the successful incorporation of Au NPs into Zn‐MOF and its viability for the electrocatalytic reactions.…”
Section: Resultsmentioning
confidence: 99%
“…3 RESULTS AND DISCUSSION The AuPd/C employed in this study, as well as the reference Au/C and Pd/C, are synthesized through a sol-immobilization method and have a nominal metal loading of 10wt%. In our previous publication, we characterized the dissolution behavior of AuPd particles immobilized directly onto an electrode as a model system 30,31 . In particular, we showed that the difference in Pd and Au dissolution onset potentials (ca.…”
Section: Tem Characterizationmentioning
confidence: 99%
“…Evidence of the surface change induced by dissolution is supported by the CVs recorded in Ar saturated electrolytes ( Figure 1b). Indeed, once the upper potential limit (UPL) is sufficiently high (above Au oxide formation 30 , ca. 1.5 VRHE) two distinct peaks are observable on the reverse scan: Pd oxide and Au oxide reduction.…”
Section: Tem Characterizationmentioning
confidence: 99%
“…For example, the introduction of a secondary metal (e.g., Au, Ir, Cu, etc.) at a certain concentration to form alloys or intermetallics can improve not only the activity but also the chemical stability of the Pd‐based catalysts through ensemble and electronic effects . The improvement of thermal and mechanical stabilities can be achieved through the fabrication of Pd‐based nanoarchitectures with higher dimensions (1D, 2D, and 3D), since they have lower vulnerability to dissolution, the Ostwald ripening, and aggregation during the reactions compared to 0D nanoparticles .…”
Section: Introductionmentioning
confidence: 99%